Exhaust gas purification catalyst

The exhaust gas purification catalyst addresses the challenge of precious metal reduction and HC poisoning by employing a structured coat layer with localized Rh and supported Pd/Pt on Al2O3, enhancing both HC and NOx purification efficiency and warm-up performance.

JP2025009140APending Publication Date: 2025-01-20TOYOTA JIDOSHA KK +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023111936
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing exhaust gas purification catalysts face challenges in reducing the amount of precious metals while maintaining catalytic activity and improving warm-up performance, particularly in rich air-fuel ratio atmospheres where HC poisoning is prevalent.

Method used

The catalyst structure includes a lower coat layer with locally arranged Rh and an upper coat layer containing Pd and/or Pt supported on Al2O3, with specific thickness and particle size ratios to enhance gas diffusivity and prevent alloying, thereby improving HC and NOx purification performance.

Benefits of technology

The catalyst effectively suppresses HC poisoning and enhances warm-up performance by optimizing the distribution and support of noble metals, ensuring efficient purification of harmful components in varying atmospheric conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009140000001_ABST
    Figure 2025009140000001_ABST
Patent Text Reader

Abstract

To provide an exhaust gas purification catalyst having improved warming-up properties while suppressing HC poisoning of precious metals in an atmosphere which is susceptible to HC poisoning and has a rich air-fuel ratio.SOLUTION: There is provided an exhaust gas purification catalyst having a base material and a catalyst coat layer coated on the base material, wherein the catalyst coat layer has a lower coat layer coated on the base material and an upper coat layer coated on the lower coat layer, the upper coat layer contains Pd and / or Pt and a first carrier particle, the first carrier particle contains Al2O3, a certain amount or more of the Pd and / or Pt contained in the upper coat layer is supported on the Al2O3, a thickness of the upper coat layer is adjusted, the lower coat layer contains Rh and second carrier particles, an average particle diameter D50 of the second carrier particles is specified and the Rh contained in the lower coat layer is locally disposed.SELECTED DRAWING: Figure 7
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for purifying exhaust gas. [Background technology]

[0002] 2. Description of the Related Art Exhaust gas discharged from internal combustion engines for automobiles and the like, such as gasoline engines or diesel engines, contains harmful components, such as carbon monoxide (CO), hydrocarbons (HC), and nitrogen oxides (NOx).

[0003] For this reason, internal combustion engines are generally equipped with exhaust gas purification devices to decompose and remove these harmful components, and these harmful components are almost all rendered harmless by exhaust gas purification catalysts installed in these exhaust gas purification devices.

[0004] For example, Patent Document 1 discloses a catalyst comprising a honeycomb carrier and a catalyst layer provided on the honeycomb carrier, the catalyst layer comprising precious metal particles, a plurality of first compounds on which the precious metal particles are supported, the first compounds being an oxide containing Ce or a composite oxide of Mn and Al, and a second compound which covers the plurality of first compounds supporting the precious metal particles, separates the first compounds from each other, and is an oxide containing at least one of Al and Zr, the pore volume of the catalyst layer being 0.24 to 0.8 cm 3 / g, and the particle size of the second compound is within a range of 10 to 100 nm.

[0005] Patent Document 2 discloses an exhaust gas purifying catalyst comprising a substrate and a catalyst coating layer formed on the surface of the substrate, the catalyst coating layer including upper and lower layers with a lower layer being closer to the substrate surface and an upper layer being relatively farther from the substrate surface, the upper layer of the catalyst coating layer containing Rh and Pd and a carrier, the upper layer of the catalyst coating layer including a Pd outermost layer having a relatively higher Pd concentration than other parts of the upper layer on a surface area of ​​20 mm or more downstream from the upstream end, the lower layer of the catalyst coating layer containing at least one precious metal selected from Pd and Pt and a carrier, and 60 mass % or more of the Pd contained in the outermost Pd layer is present in a layer from the surface of the outermost Pd layer relatively far from the substrate surface to 50% of the thickness of the upper layer. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2007-313498 A [Patent Document 2] JP 2019-069402 A Summary of the Invention [Problem to be solved by the invention]

[0007] The amount of precious metal contained in each catalyst coating layer is required to be reduced from the viewpoint of resource risk. In order to reduce the amount of precious metal, it is necessary to prevent the catalytic activity of the precious metal from decreasing due to use of the exhaust gas purification catalyst. In order to prevent the catalytic activity of the precious metal from decreasing, for example, it is possible to suppress the poisoning of the precious metal by HC in the exhaust gas (HC poisoning), which is one of the factors that decrease the catalytic activity of the precious metal.

[0008] On the other hand, catalysts for purifying exhaust gas are also required to have good warm-up characteristics, that is, to purify exhaust gas in the initial stage of exhaust gas purification (for example, immediately after starting the engine).

[0009] Therefore, an object of the present invention is to provide an exhaust gas purification catalyst that has improved warm-up properties while suppressing HC poisoning of precious metals in an atmosphere with a rich air-fuel ratio (A / F) (oxygen-lean atmosphere) in which HC poisoning is likely to occur. [Means for solving the problem]

[0010] Each catalyst coating layer usually plays a role in purifying a different harmful component. Therefore, when an exhaust gas purification catalyst has a substrate, a lower coating layer coated on the substrate, and an upper coating layer coated on the lower coating layer, it is desired that the upper coating layer has a structure that allows the lower coating layer and exhaust gas containing harmful components to quickly come into contact with each other, that is, a structure that is excellent in gas diffusion properties.

[0011] Therefore, the present inventors have investigated various means for solving the above-mentioned problems, and as a result, have discovered that in an exhaust gas purifying catalyst having a substrate and a catalyst coating layer coated on the substrate, a lower coating layer is coated on the substrate as a catalyst coating layer, and an upper coating layer is coated on the lower coating layer, and rhodium (Rh) is locally disposed in the lower coating layer, and palladium (Pd) and / or platinum (Pt) supported on alumina (Al2O3) is introduced into the upper coating layer, the thickness of which is adjusted, thereby purifying HC in exhaust gas and converting it into a catalyst for purifying exhaust gas. The inventors have found that exhaust gas containing NOx from which HC has been purified is efficiently purified by Pd and / or Pt supported on Al2O3, which has high resistance to HC poisoning, in the upper coating layer with which the exhaust gas first comes into contact, and that the exhaust gas containing NOx from which HC has been purified is then efficiently purified by Rh, which has excellent NOx purification performance, in the lower coating layer located beyond the upper coating layer, and that the Rh locally arranged in the lower coating layer suppresses alloying between the Rh in the lower coating layer and the Pd and / or Pt in the upper coating layer, thereby improving the HC purification performance, and have completed the present invention.

[0012] That is, the gist of the present invention is as follows. (1) A catalyst for purifying exhaust gas, comprising a substrate and a catalyst coating layer coated on the substrate, The catalyst coating layer has an undercoat layer coated on the substrate and an upper coating layer coated on the undercoat layer, the upper coating layer contains Pd and / or Pt and first support particles; the first support particles comprise Al2O3; 80% by weight or more of the total weight of Pd and / or Pt contained in the upper coating layer is supported on Al2O3, The thickness ratio of the upper coat layer to the lower coat layer (upper coat layer / lower coat layer) is 0.2 or less; the lower coating layer contains Rh and second carrier particles; The average particle size D50 of the second carrier particles is 5 μm to 16 μm, The local degree of Rh contained in the lower coating layer is expressed by the following formula: Local degree of Rh = 1 / Uniform degree of Rh (In the formula, "degree of uniformity of Rh" represents 1-(number of cells with a value of 0 / total number of cells), where "number of cells with a value of 0" represents the total number of cells with a value of 0 out of the total cells in the lower, central and upper parts when a 200 x 200 cell portion is cut out from the csv data, which is the original data of the EPMA image from which Rh was extracted at 500x magnification of the lower coating layer, and a 50 x 50 cell lower, central and upper portion is cut out from the cut out portion, and "total number of cells" represents the total number of cells in the lower, central and upper parts.) is arranged so that Catalyst for purifying exhaust gas. (2) The exhaust gas purifying catalyst according to (1), wherein the average particle size D50 of the first carrier particles is equal to or greater than the average particle size D50 of the second carrier particles. (3) The exhaust gas purifying catalyst according to (1) or (2), wherein 95% by weight or more of the total weight of Pd and / or Pt contained in the upper coating layer is supported on Al2O3. (4) The exhaust gas purifying catalyst according to any one of (1) to (3), wherein the upper coat layer has a thickness of 20 μm or less. (5) A method for producing an exhaust gas purifying catalyst according to any one of (1) to (4), (i) stirring and mixing a precursor of Rh, a second support particle, and a solvent, and drying and calcining the resulting mixture to obtain Rh-loaded support particles; (ii) a step of stirring and mixing the Rh-supported support particles obtained in step (i), the second support particles not supporting Rh, and a solvent, and pulverizing the second support particles so that the average particle size D50 is 5 μm to 16 μm to prepare a catalyst coating layer slurry for a lower coating layer; (iii) applying the catalyst coating layer slurry for the undercoat layer obtained in the step (ii) onto a substrate, and drying and firing the catalyst coating layer to form an undercoat layer; (iv) preparing a catalyst coating layer slurry for an upper coating layer by stirring and mixing a precursor of Pd and / or Pt, a first support particle containing Al2O3, and a solvent; (v) a step of coating the catalyst coating layer slurry for the upper coating layer obtained in the step (iv) on the substrate on which the lower coating layer obtained in the step (iii) is formed, followed by drying and firing to form an upper coating layer; The method includes: Effect of the Invention

[0013] The present invention provides an exhaust gas purification catalyst that suppresses HC poisoning of precious metals and has improved warm-up properties in an atmosphere with a rich air-fuel ratio where HC poisoning is likely to occur. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a diagram illustrating an embodiment of the present invention. [Diagram 2] 1 is a flow chart showing the manufacturing process of Comparative Example 1 (A) and Example 1 (B). [Diagram 3] 3 is a photograph showing the results of analyzing, by EPMA, the catalyst coating layers of the exhaust gas purifying catalysts of Comparative Example 1 and Examples 1 to 3. [Figure 4] FIG. 1 shows EPMA images (A) and the original csv data (B) for Rh in Comparative Examples 1 and 2 and Examples 1 to 3. [Diagram 5]FIG. 2 is a diagram showing EPMA images of Rh in Comparative Examples 1 and 2 and Examples 1 to 3, and the local degree of Rh. [Figure 6] 1 is a graph showing HC emissions in Comparative Example 1 and Examples 1 to 3. [Figure 7] 1 is a graph showing the relationship between the average particle size D50 of the carrier particles in the lower coat layer and the HC emissions in Comparative Examples 1 and 2 and Examples 1 and 3 to 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] In the following, preferred embodiments of the present invention are described in detail. In this specification, the features of the present invention will be described with reference to the drawings as appropriate. In the drawings, the dimensions and shapes of each part are exaggerated for clarity, and the actual dimensions and shapes are not accurately depicted. Therefore, the technical scope of the present invention is not limited to the dimensions and shapes of each part shown in these drawings. The exhaust gas purification catalyst of the present invention is not limited to the following embodiments, and can be embodied in various forms with modifications, improvements, etc. that a person skilled in the art can make without departing from the gist of the present invention.

[0016] (base material) The substrate is a substrate having a gas flow passage through which exhaust gas flows. As the substrate, a substrate having a known honeycomb shape can be used, and specifically, a monolith substrate having a honeycomb shape (honeycomb filter, high density honeycomb, etc.) can be mentioned. In addition, the material of such a substrate is not limited, but can be a substrate made of ceramics such as cordierite, silicon carbide, silica, alumina, mullite, etc., or a substrate made of metal such as stainless steel containing chromium and aluminum. From the viewpoint of cost, cordierite is preferable as the material of the substrate.

[0017] (Catalyst Coating Layer) The catalyst coating layer has at least a lower coating layer coated on the substrate, and an upper coating layer coated on the lower coating layer.

[0018] The thickness of the lower coating layer is not limited as long as it satisfies the thickness ratio of the upper coating layer to the lower coating layer (upper coating layer / lower coating layer) described below, but is usually 20 μm to 100 μm, preferably 30 μm to 80 μm. In this specification, the thickness refers to the average thickness, for example, the average value of the thicknesses of 10 randomly selected points in an image of the coating layer such as SEM or TEM.

[0019] By setting the thickness of the lower coating layer within the above range, it is possible to suppress aggregation of catalytic metals due to an excessively thin thickness, for example aggregation of catalytic metals due to high density of the catalytic metals, while improving the frequency of contact between the catalytic metals contained in the lower coating layer and harmful components in the exhaust gas, such as NOx, thereby improving the exhaust gas purification performance, and furthermore, it is possible to maintain a good balance between pressure loss, catalytic performance, and durability in the exhaust gas purification catalyst.

[0020] The thickness of the upper coating layer is not limited as long as the thickness ratio of the upper coating layer to the lower coating layer (upper coating layer / lower coating layer) described below is satisfied, but is usually 20 μm or less, preferably 1 μm to 20 μm, and more preferably 1 μm to 10 μm.

[0021] By having the thickness of the upper coating layer within the above range, it is possible to suppress a decrease in gas diffusion properties of exhaust gas due to an excessively thick thickness, and to increase the frequency of contact between the exhaust gas and the lower coating layer that is located after the exhaust gas has passed through the upper coating layer. As a result, harmful components in the exhaust gas that were not completely purified by the upper coating layer, such as NOx, can be quickly and efficiently purified in the lower coating layer.

[0022] When the catalyst coating layer has a lower coating layer and an upper coating layer, the upper coating layer can efficiently purify HC, and the lower coating layer can efficiently purify NOx.

[0023] The thickness ratio of the upper coating layer to the lower coating layer (upper coating layer / lower coating layer) is 0.2 or less, and preferably 0.01 to 0.16.

[0024] When the thickness ratio of the upper coat layer to the lower coat layer (upper coat layer / lower coat layer) falls within the above range, HC purification and NOx purification in a rich atmosphere can be efficiently performed.

[0025] (Upper coat layer) The upper coat layer contains Pd and / or Pt as a catalytic metal and first support particles.

[0026] By including Pd and / or Pt in the upper coating layer, exhaust gas, particularly HC, immediately after being discharged from an engine or the like comes into contact with Pd and / or Pt, thereby improving the performance of purifying HC in the exhaust gas.

[0027] The content (total weight) of Pd and / or Pt contained in the upper coating layer is not limited, but is usually 0.1 g to 5.0 g, preferably 0.2 g to 3.0 g, calculated as the metal of the catalytic metal per 1 L of the substrate volume. The content of the components contained in the exhaust gas purifying catalyst depends on the amount of materials added (excluding the components to be volatilized) during the production of the exhaust gas purifying catalyst, and the explanation thereof will be omitted below.

[0028] When the upper coating layer contains Pd and / or Pt in the above-mentioned amount, the ignition property is improved due to the high density of Pd and / or Pt, and therefore the purification performance of exhaust gas, particularly HC, can be improved.

[0029] The first support particles included in the upper coating layer include Al2O3. The first support particles included in the upper coating layer may be made of Al2O3.

[0030] The Al2O3 contained in the first support particles supports, in whole or in part, the Pd and / or Pt contained in the upper coat layer.

[0031] On the other hand, 80 wt % or more, preferably 90 wt % or more, more preferably 95 wt % or more, even more preferably 99 wt % or more, and particularly approximately 100 wt % of the total weight of Pd and / or Pt contained in the upper coating layer is supported on Al2O3.

[0032] The method of supporting Pd and / or Pt on Al2O3 can be a method generally used in the technical field of exhaust gas purification catalysts, for example, a method of mixing precursors of Pd and / or Pt, Al2O3, and a solvent such as water in a vessel with stirring, and optionally filtering the resulting mixture, and further drying and calcining it.

[0033] By supporting most of the Pd and / or Pt contained in the upper coat layer on Al2O3, Pd and / or Pt can efficiently purify HC while suppressing HC poisoning by Al2O3, which has excellent resistance to HC poisoning.

[0034] The content of the first carrier particles or Al2O3 contained in the upper coat layer is not limited, but is usually 3 g to 40 g, and preferably 5 g to 30 g, per 1 L of the volume of the substrate.

[0035] When the upper coating layer contains the first carrier particles or Al2O3 in the above-mentioned amount, the HC purification performance can be improved by improving the ignition ability due to the high density of Pd and / or Pt, while the HC poisoning resistance of the Pd and / or Pt supported on the Al2O3 can be sufficiently improved.

[0036] The coating amount of the upper coating layer is not limited, but is usually 3 g to 50 g, and preferably 5 g to 50 g, per 1 L of the substrate volume.

[0037] By setting the amount (coating amount) of each material in the upper coating layer within the above range, the gas diffusion in the upper coating layer is improved, and further, the warming-up performance is improved by increasing the frequency of contact of exhaust gas with the lower coating layer. The purification performance of exhaust gas, particularly HC, can be improved by improving ignition performance due to the high density of Pd and / or Pt, and the purification performance of harmful components other than HC, such as NOx, due to the precious metals contained in the lower coating layer can be improved.

[0038] The type and size of the particles contained in the upper coat layer, particularly the first carrier particles or Al2O3, are not limited. The average particle size D50 of the particles contained in the upper coat layer, particularly the first carrier particles or Al2O3, is usually 5 μm to 16 μm, preferably 5 μm to 12 μm. The average particle size D50 of the first carrier particles or Al2O3 is preferably equal to or greater than the average particle size D50 of the second carrier particles described below.

[0039] Here, the average particle size D50 means the particle size at 50% volume in a cumulative volume distribution curve in a volume-based particle size distribution obtained by measurement using a laser diffraction scattering method, with the total volume being 100% (i.e., the volume-based cumulative 50% diameter).

[0040] By including Al2O3 or the first carrier particles having an average particle size D50 in the above-mentioned range in the upper coating layer, the HC poisoning resistance of Pd and / or Pt supported on Al2O3 can be improved, and the intrusion of Pd and / or Pt into the lower coating layer during the production and use of the exhaust gas purification catalyst can be suppressed.

[0041] The upper coating layer is preferably composed of Pd and / or Pt and Al2O3 carrying Pd and / or Pt.

[0042] Since the upper coating layer is composed of Pd and / or Pt and Al2O3 carrying Pd and / or Pt, HC in the exhaust gas can be efficiently purified while avoiding HC poisoning by the Pd and / or Pt, and further, the exhaust gas from which HC has been purified can be quickly guided to the lower coating layer located below the upper coating layer, and can be efficiently purified in the lower coating layer.

[0043] (Lower coat layer) The undercoat layer contains Rh as a catalytic metal and second support particles.

[0044] The content of Rh contained in the lower coating layer is not limited, but is usually 0.05 g to 1.0 g, and preferably 0.2 g to 0.8 g, calculated as Rh metal per 1 L of the substrate volume.

[0045] When the lower coating layer contains Rh in the above amount, Rh and the like which are easily poisoned by HC are not poisoned by HC in an atmosphere in which HC has been sufficiently purified by the upper coating layer, and harmful components other than HC that could not be purified by the upper coating layer, particularly NOx, can be efficiently and sufficiently purified.

[0046] The lower coating layer further includes second carrier particles. The second carrier particles include any metal oxide generally used in the technical field of exhaust gas purification catalysts, such as SiO2, MgO, ZrO2, CeO2, Al2O3, TiO2, Y2O3, Nd2O3, La2O3, and composite oxides or solid solutions of two or more of them, such as Al2O3-CeO2-ZrO2 composite oxide (ACZ), CeO2-ZrO2 composite oxide (CZ), and Al2O3-ZrO2 composite oxide (AZ) (the ratio of each oxide in the composite oxides, such as ACZ, CZ, and AZ, is not limited and may be the ratio generally used in the technical field of exhaust gas purification catalysts), and combinations of two or more of them.

[0047] Acidic carriers, for example, SiO2, are compatible with catalytic metals that reduce NOx. Basic carriers, for example, MgO, are compatible with potassium (K) and barium (Ba) that occlude NOx. ZrO2 suppresses the sintering of other carrier particles at high temperatures at which other carrier particles are sintered, and when combined with, for example, Rh as a catalytic metal, it generates H2 by a steam reforming reaction, and can efficiently reduce NOx. Since acid-base amphoteric carriers, for example, Al2O3, have a high specific surface area, they can be used to efficiently occlude and reduce NOx. TiO2 can exert an effect of suppressing sulfur poisoning of catalytic metals. ACZ and CZ are materials (OSC materials) that have oxygen storage capacity (OSC), and can keep the oxygen concentration constant and maintain the purification performance of exhaust gas purification catalysts even when the air-fuel ratio fluctuates. In addition, the addition of Al2O3, ZrO2, and other metal oxides can increase the durability of the support.

[0048] It should be understood that, according to the characteristics of the support particles described above, the exhaust gas purification performance, particularly the NOx purification performance, of the exhaust gas purification catalyst of the present invention may be improved depending on the type, composition, combination and ratio and / or amount of the support particles selected.

[0049] The content of the second carrier particles in the lower coating layer is not limited, but is usually 50 g to 300 g, and preferably 100 g to 200 g, per 1 L of the volume of the base material.

[0050] Although Rh and other precious metals contained in the lower coating layer function as catalytic metals in an exhaust gas purification catalyst as they are, they are usually supported on second carrier particles.

[0051] When Rh and other precious metals are supported on the second support particles, the specific surface area of ​​the support particles is large, so that the contact area between the exhaust gas and the precious metals can be increased, thereby improving the performance of the exhaust gas purification catalyst.

[0052] As a method for supporting Rh and other precious metals on the second support particles, a method generally used in the technical field of exhaust gas purification catalysts can be used.

[0053] The Rh contained in the undercoat layer is unevenly distributed in the undercoat. In one embodiment, in order to unevenly distribute and localize Rh in the undercoat layer, the second support particles contained in the undercoat layer include those that support Rh and those that do not support Rh. Here, the ones that support Rh and those that do not support Rh may be of the same composition (material) or different compositions (materials).

[0054] The uneven distribution of Rh in the lower coating layer (the local degree of Rh) is the inverse of the uniformity of Rh, that is, the local degree of Rh expressed by the following formula: Local degree of Rh = 1 / Uniform degree of Rh (In the formula, "degree of uniformity of Rh" represents 1-(number of cells with a value of 0 / total number of cells), where "number of cells with a value of 0" represents the total number of cells with no Rh present among the total cells in the lower, central and upper parts when a 200 x 200 cell portion is cut out from the csv data, which is the original data of the EPMA image from which Rh is extracted at 500x magnification of the lower coating layer, and a 50 x 50 cell lower, central and upper portion is cut out from the cut out portion, and "total number of cells" represents the total number of cells in the lower, central and upper parts, i.e., 50 x 50 x 3 = 7500.) For a calculation example of the local degree of Rh, see the Examples.

[0055] In the present invention, Rh in the lower coating layer is arranged so that the local degree of Rh is 1.47 to 2.10.

[0056] By locally disposing Rh in the lower coating layer, the distance between Rh in the lower coating layer and Pd and / or Pt in the upper coating layer can be increased, reducing the frequency of contact between them and suppressing alloying of Rh with Pd and / or Pt due to durability, thereby improving the HC purification performance after durability testing.

[0057] The coating amount of the lower coating layer is not limited, but is usually 50 g to 350 g, and preferably 100 g to 250 g, per 1 L of the substrate volume.

[0058] When the amount (coating amount) of each material in the lower coating layer falls within the above range, a good balance between pressure loss, catalytic performance, and durability in the exhaust gas purifying catalyst can be maintained.

[0059] The particles contained in the lower coat layer, particularly the second carrier particles, have an average particle size D50 of 5 μm to 16 μm, preferably 5 μm to 12 μm.

[0060] By setting the average particle diameter D50 of the second carrier particles within the above range, the Rh contained in the lower coat layer can be locally arranged as described above.

[0061] FIG. 1 shows a schematic diagram of one embodiment of the present invention. In FIG. 1, a catalyst coating layer 2 is formed on a substrate 1. The catalyst coating layer 2 is composed of a lower coating layer 3 formed on the substrate 1 and an upper coating layer 4 formed on the lower coating layer 3. Rh is present locally in the lower coating layer 3. On the other hand, Pd is supported on Al2O3 and is present only in the upper coating layer 4. The size of the Al2O3 as the first carrier particles is equal to or larger than that of the second carrier particles.

[0062] (Method of manufacturing exhaust gas purification catalyst) The exhaust gas purifying catalyst of the present invention can be produced by using the configuration of the exhaust gas purifying catalyst described above, and by using a known coating technique, except that Rh is locally arranged in the lower coating layer, for example, the lower coating layer is formed using a lower coating layer slurry containing Rh, second support particles carrying all of the Rh, and second support particles carrying no Rh.

[0063] The exhaust gas purifying catalyst of the present invention can be produced, for example, as follows. First, a catalyst coating layer slurry for the undercoat layer is applied to an area of ​​the substrate where the undercoat layer is to be formed, for example, by suction.

[0064] The catalyst coating layer slurry for the lower coating layer can be prepared by stirring and mixing the materials constituting the lower coating layer, i.e., the second carrier particles carrying Rh (Rh-carrying carrier particles), the second carrier particles not carrying Rh, for example, an alumina-ceria-zirconia composite oxide, a solvent, for example, water, alcohol, a mixture of water and alcohol, and additives, for example, a thickener, and further pulverizing the second carrier particles contained in the lower coating layer so that the average particle size D50 falls within the above range. The Rh-carrying carrier particles can be prepared by, for example, drying a mixture containing a precursor of Rh, for example, a salt containing Rh, for example, a nitrate salt, the second carrier particles, for example, an alumina-zirconia composite oxide, and a solvent, for example, water, alcohol, a mixture of water and alcohol, in the atmosphere, for example, at 100°C to 150°C, for 1 hour to 3 hours to remove the solvent, and then calcining the mixture in the atmosphere, for example, at 450°C to 550°C, for 1 hour to 3 hours.

[0065] After the excess slurry is blown off with a blower or the like, the mixture is dried, for example, in the atmosphere, typically at 100°C to 150°C, typically for 1 hour to 3 hours to remove the solvent, and then fired in the atmosphere, typically at 450°C to 550°C, typically for 1 hour to 3 hours to form an undercoat layer.

[0066] Next, a catalyst coating layer slurry for an upper coating layer is applied, for example, by suction, to a region on the lower coating layer of the substrate on which the lower coating layer has been formed, where an upper coating layer is to be formed.

[0067] The catalyst coating layer slurry for the upper coating layer can be prepared by stirring and mixing the materials constituting the upper coating layer, i.e., precursors of Pd and / or Pt, such as salts containing Pd and / or Pt, such as nitrates, Al2O3 as the first carrier particles, solvents such as water, alcohol, a mixture of water and alcohol, and additives such as thickeners, and further pulverizing the first carrier particles contained in the upper coating layer so that the average particle size D50 is equal to or greater than the average particle size D50 of the second carrier particles contained in the lower coating layer. The catalyst coating layer slurry preparation process for the upper coating layer can be performed at any time before the application of the catalyst coating layer slurry for the upper coating layer, and may be performed, for example, before preparing the catalyst coating layer slurry for the lower coating layer.

[0068] After the excess slurry is blown off with a blower or the like, the solvent is removed by drying, for example, in the atmosphere, typically at 100°C to 150°C, typically for 1 hour to 3 hours, and then calcination is performed in the atmosphere, typically at 450°C to 550°C, typically for 1 hour to 3 hours to form an upper coat layer, thereby producing a catalyst for purifying exhaust gas.

[0069] (Use of exhaust gas purification catalyst) The exhaust gas purifying catalyst of the present invention can exhibit a significant effect in exhaust gas purification performance in a rich atmosphere, and can be used even in an environment in which excess HC, etc. in a rich atmosphere are adsorbed to the exhaust gas purifying catalyst and may poison the exhaust gas purifying catalyst, and can be used as an exhaust gas purifying catalyst that exhibits a high HC poisoning suppression effect and has excellent warm-up properties. EXAMPLES

[0070] Several examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.

[0071] 1. Preparation of exhaust gas purification catalyst Comparative Example 1 (1) First, Rh nitrate (material 1), Al2O3-CeO2-ZrO2 composite oxide (Al2O3: 30% by weight, CeO2: 20% by weight, ZrO2: 50% by weight) (material 2), Al2O3-ZrO2 composite oxide (Al2O3: 30% by weight, ZrO2: 70% by weight) (material 3), Al2O3 (material 4), Al2O3-based binder, thickener (hydroxyethyl cellulose), and organic fiber were added to distilled water while stirring, and the mixture was stirred and pulverized to prepare a suspended catalyst coating layer slurry (slurry 1) for the lower coating layer with an average particle size D50 of approximately 5 μm.

[0072] (2) Next, the prepared slurry 1 was poured into the substrate (NGK honeycomb substrate of 875 cc (600 cells, hexagonal, wall thickness 2 mil)) by suction, and unnecessary parts were blown away with a blower to coat the substrate wall with the material, thereby preparing the precursor layer of the lower coating layer. At that time, for each coating material, the amount of Rh was 0.25 g for material 1, 99 g for material 2, 41 g for material 3, and 45 g for material 4 per 1 L of substrate volume. In addition, the precursor layer of the lower coating layer was applied from the upstream end to the downstream end in the exhaust gas flow direction of the exhaust gas purification catalyst, that is, over the entire length of the substrate of the exhaust gas purification catalyst (coat width: 100%).

[0073] (3) The substrate coated with the precursor layer of the undercoat layer was dried in a dryer maintained at 120°C for 2 hours to remove moisture, and then fired in an electric furnace maintained at 500°C for 2 hours to prepare the undercoat layer.

[0074] (4) Next, in the same manner as in (1), Pd nitrate (material 5), Al2O3 (material 4), and a thickener (hydroxyethyl cellulose) were added to distilled water while stirring, and the mixture was stirred and pulverized to prepare a suspended catalyst coating layer slurry (slurry 2) for the upper coating layer having an average particle size D50 of approximately 5 μm.

[0075] (5) Next, the prepared slurry 2 was poured by suction onto the outermost surface of the lower coating layer of the substrate with the lower coating layer, and unnecessary parts were blown away with a blower to coat the material on the substrate wall surface, thereby preparing the precursor layer of the upper coating layer. At that time, for each coating material, the amount of material 5 was 0.15 g as Pd and the amount of material 4 was 6 g per 1 L of substrate volume. In addition, the coating width of the precursor layer of the upper coating layer was 100%.

[0076] (6) Finally, the substrate having the precursor layer of the upper coating layer applied onto the lower coating layer was dried for 2 hours in a dryer maintained at 120°C to remove moisture, and then fired for 2 hours in an electric furnace maintained at 500°C to prepare the upper coating layer and the exhaust gas purification catalyst.

[0077] FIG. 2A shows a production flow chart of Comparative Example 1.

[0078] Example 1 (1) First, Rh nitrate (material 1) and Al2O3-ZrO2 composite oxide (material 3) were added to distilled water while stirring. After stirring and mixing, the mixture was dried for 2 hours in a dryer maintained at 120°C to remove moisture, and then fired for 2 hours in an electric furnace maintained at 500°C to prepare an Al2O3-ZrO2 composite oxide loaded with Rh. (2) Next, the Rh-loaded Al2O3-ZrO2 composite oxide prepared in (1), the Al2O3-CeO2-ZrO2 composite oxide (material 2), Al2O3 (material 4), an Al2O3-based binder, a thickener (hydroxyethyl cellulose), and organic fibers were added to distilled water with stirring, and the mixture was stirred and pulverized to prepare a suspended catalyst coating layer slurry (slurry 3) for the lower coating layer with an average particle size D50 of approximately 5 μm.

[0079] (3) Next, the prepared slurry 3 was poured into the substrate (NGK honeycomb substrate of 875 cc (600 cells, hexagonal, wall thickness 2 mil)) by suction, and unnecessary parts were blown away with a blower to coat the substrate wall with the material, thereby preparing the precursor layer of the lower coating layer. At that time, for each coating material, the amount of Rh was 0.25 g for material 1, 99 g for material 2, 41 g for material 3, and 45 g for material 4 per 1 L of substrate volume. The coating width of the precursor layer of the lower coating layer was set to 100%.

[0080] (4) The substrate coated with the precursor layer of the undercoat layer was dried in a dryer maintained at 120°C for 2 hours to remove moisture, and then fired in an electric furnace maintained at 500°C for 2 hours to prepare the undercoat layer.

[0081] (5) Next, in the same manner as in (2), Pd nitrate (material 5), Al2O3 (material 4), and a thickener (hydroxyethyl cellulose) were added to distilled water while stirring, and the mixture was stirred and pulverized to prepare a suspended catalyst coating layer slurry (slurry 2) for the upper coating layer having an average particle size D50 of approximately 5 μm.

[0082] (6) Next, the prepared slurry 2 was poured by suction onto the outermost surface of the lower coating layer of the substrate provided with the lower coating layer in (4), and unnecessary material was blown away with a blower to coat the material on the substrate wall, thereby preparing the precursor layer of the upper coating layer. At that time, for each coating material, the amount of material 5 was 0.15 g (0.15 g / L) as Pd and the amount of material 4 was 6 g (6 g / L) per 1 L of substrate volume. In addition, the coating width of the precursor layer of the upper coating layer was 100%.

[0083] (7) Finally, the substrate having the precursor layer of the upper coating layer applied onto the lower coating layer was dried for 2 hours in a dryer maintained at 120°C to remove moisture, and then fired for 2 hours in an electric furnace maintained at 500°C to prepare the upper coating layer and the exhaust gas purification catalyst.

[0084] FIG. 2B shows a production flow chart of the first embodiment.

[0085] Example 2 In Example 1, instead of the slurry 3 used in (2) and (3), a catalyst coating layer slurry (slurry 4) for a suspended lower coating layer having an average particle size D50 of about 12 μm, which was prepared by shortening the pulverization time in (2), was used, and the lower coating layer was adjusted to be in a sparser state than in Example 1. An exhaust gas purification catalyst was prepared in the same manner as in Example 1.

[0086] Example 3 In Example 1, instead of the slurry 3 used in (2) and (3), a catalyst coating layer slurry (slurry 4) for a suspended lower coating layer having an average particle size D50 of about 12 μm, which was prepared by shortening the grinding time in the grinding step in (2), was used to adjust the lower coating layer to be coarser than in Example 1, and instead of the slurry 2 used in (5) and (6), a catalyst coating layer slurry (slurry 5) for a suspended lower coating layer having an average particle size D50 of about 12 μm, which was prepared by shortening the grinding time in the grinding step in (5), was used to adjust the upper coating layer to be coarser than in Examples 1 and 2. An exhaust gas purification catalyst was prepared in the same manner as in Example 1.

[0087] Example 4 In Example 1, instead of the slurry 3 used in (2) and (3), a catalyst coating layer slurry (slurry 6) for a suspended lower coating layer having an average particle size D50 of about 8 μm, which was prepared by shortening the grinding time in the grinding in (2), was used, and the lower coating layer was adjusted to be in a sparser state than in Example 1 and in a denser state than in Examples 2 and 3. In place of the slurry 2 used in (5) and (6), a catalyst coating layer slurry (slurry 7) for a suspended lower coating layer having an average particle size D50 of about 8 μm, which was prepared by shortening the grinding time in the grinding in (5), was used, and the upper coating layer was adjusted to be in a sparser state than in Examples 1 and 2 and in a denser state than in Example 3. An exhaust gas purification catalyst was prepared in the same manner as in Example 1.

[0088] Example 5 In Example 1, instead of the slurry 3 used in (2) and (3), a catalyst coating layer slurry (slurry 8) for a suspended lower coating layer having an average particle size D50 of about 16 μm, which was prepared by shortening the grinding time in the grinding step in (2), was used, and the lower coating layer was adjusted to be in a coarser state than in Examples 1 to 4. In place of the slurry 2 used in (5) and (6), a catalyst coating layer slurry (slurry 9) for a suspended lower coating layer having an average particle size D50 of about 16 μm, which was prepared by shortening the grinding time in the grinding step in (5), was used, and the upper coating layer was adjusted to be in a coarser state than in Examples 1 to 4. An exhaust gas purification catalyst was prepared in the same manner as in Example 1.

[0089] Comparative Example 2 In Example 1, instead of the slurry 3 used in (2) and (3), a catalyst coating layer slurry (slurry 10) for a suspended lower coating layer having an average particle size D50 of about 20 μm, which was prepared by shortening the grinding time in the grinding step in (2), was used, and the lower coating layer was adjusted to be in a coarser state than in Examples 1 to 5. In place of the slurry 2 used in (5) and (6), a catalyst coating layer slurry (slurry 11) for a suspended lower coating layer having an average particle size D50 of about 20 μm, which was prepared by shortening the grinding time in the grinding step in (5), was used, and the upper coating layer was adjusted to be in a coarser state than in Examples 1 to 5. An exhaust gas purification catalyst was prepared in the same manner as in Example 1.

[0090] 2. Electron probe microanalyzer (EPMA) analysis The surfaces of the exhaust gas purifying catalysts of Comparative Example 1 and Examples 1 to 3 were analyzed by EPMA (500x magnification), and the results are shown in FIG.

[0091] As can be seen from FIG. 3, in Comparative Example 1, Pd was disposed only near the surface and Rh was disposed uniformly throughout the entire catalyst coating layer; in Example 1, Pd was disposed only near the surface and Rh was disposed locally throughout the entire catalyst coating layer; in Example 2, Pd was disposed not only in the upper coating layer (outermost layer) but also partially in the lower coating layer throughout the entire catalyst coating layer, with Rh being disposed more locally than in Example 1; and in Example 3, Pd was disposed only near the surface and Rh was disposed more locally than in Example 1 throughout the entire catalyst coating layer.

[0092] The results of EPMA confirmed the following. In the lower coat layer, it was qualitatively confirmed that the Rh arrangement in Example 1, in which the average particle diameter D50 is about 5 μm, and in Examples 2 and 3, in which the average particle diameter D50 is about 12 μm, is more localized in Examples 2 and 3, and the distance between Pd and Rh is greater. It was also confirmed that a part of Pd is arranged in the lower coat layer in Example 2. This is presumably because the average particle diameter D50 of the lower coat layer is about 12 μm, while the average particle diameter of the upper coat layer is small at about 5 μm, and the Pd entered the gaps between the carrier particles of the lower coat layer when the upper coat layer was coated. In order to arrange Pd only in the upper coat layer, it is considered that the average particle diameter D50 of the upper coat layer is equal to or greater than the average particle diameter D50 of the lower coat layer.

[0093] 3. Quantification experiment of the local concentration of Rh in the lower coating layer To quantify the local concentration of Rh in the undercoat layer, the following calculations were performed.

[0094] In the EPMA images (FIG. 4(A)) of Rh in Comparative Examples 1 and 2 and Examples 1 to 3, the bottom, center, and top (each 50 cells×50 cells) were arbitrarily cut out from the CSV data (200 cells×200 cells) (FIG. 4(B)) on which the EPMA images were based, as shown in FIG. 4, and the number of cells with a numerical value of 0, i.e., cells where Rh was not present, was calculated, and the degree of uniformity of Rh was calculated using the following formula. Rh uniformity = 1-(number of 0 cells / total number of cells) (In the formula, "number of 0 cells" refers to the total number of cells showing a value of 0 among the total cells in the lower, central, and upper parts, and "total number of cells" refers to the total number of cells in the lower, central, and upper parts (50 x 50 x 3).)

[0095] The local degree of Rh can be expressed as the reciprocal of the uniformity of Rh, and is defined as follows: Local degree of Rh = 1 / Uniform degree of Rh

[0096] From the original csv data of each EPMA image, the degree of localization of Rh in the lower coating layer was calculated by the above-mentioned method, and the results are shown in Figure 5. In terms of the degree of localization of Rh, a value of 1 indicates that Rh is completely uniformly arranged, and the larger the value, the more locally Rh is arranged. From Figure 5, it was found that Example 1 is quantitatively more locally arranged than Comparative Example 1, and further, the values ​​increase in order from Example 2 to Example 3 to Comparative Example 2, indicating that Rh is more locally arranged.

[0097] 4. Durability test The exhaust gas purifying catalysts of Comparative Examples 1 and 2 and Examples 1 to 5 were subjected to the following durability test using an actual engine.

[0098] Each exhaust gas purification catalyst was installed in the exhaust system of a V8 engine, and exhaust gas in stoichiometric and lean atmospheres was repeatedly passed through the catalyst at a catalyst bed temperature of 950°C for 50 hours for a fixed period of time (3:1 ratio).

[0099] 5. Engine bench evaluation 4. Durability Tests were Carried Out With respect to the exhaust gas purifying catalysts of Comparative Examples 1 and 2 and Examples 1 to 5, evaluation of the HC emission behavior in a rich atmosphere was carried out using an actual engine.

[0100] (1) First, an L-type 4-cylinder engine was started and the engine conditions were adjusted so that the inlet gas temperature was 550°C. (2) Each exhaust gas purification catalyst was installed in the exhaust system of the engine. Once stabilized, the air-fuel ratio (A / F) was alternately varied at three-minute intervals between A / F 14.1 (rich condition) and A / F 15.1 (lean condition). (3) HC emissions were evaluated 3 minutes after the third A / F switch from 15.1 (lean) to 14.1 (rich).

[0101] 6. Engine bench evaluation results Table 1 shows the results of Comparative Examples 1-2 and Examples 1-5.

[0102] [Table 1]

[0103] FIG. 6 shows the results of Comparative Example 1 and Examples 1 to 3. From Table 1 and FIG. 6, it was found that Example 1 had a suppressed amount of HC emissions after the durability test compared to Comparative Example 1. This is presumed to be because the change from uniform arrangement of Rh to local arrangement suppressed the alloying of Pd and Rh during the durability test, improving the utilization efficiency of Pd. Furthermore, it was found that Example 3 had a suppressed amount of HC emissions after the durability test compared to Example 1. This is presumed to be because, in conjunction with the results of EPMA, the arrangement of Rh became more localized by increasing the average particle diameter D50 of the lower coating layer, and the distance from Pd became wider, making it more difficult to alloy. Furthermore, it was found that Example 2 had a suppressed amount of HC emissions after the durability test compared to Comparative Example 1, but increased compared to Example 1. This, together with the EPMA results, is thought to be because when the average particle size D50 of the upper coating layer is smaller than that of the lower coating layer, part of the Pd penetrates into the lower coating layer during coating of the upper coating layer, and because (1) the penetrated Pd becomes more likely to alloy with Rh, and (2) contact with exhaust gas becomes poor, the HC purification performance does not improve significantly even if the Rh is more locally arranged. Therefore, in order to prevent the Pd in ​​the upper coating layer from penetrating into the lower coating layer, it is desirable that the average particle size D50 of the carrier particles in the upper coating layer be equal to or greater than the average particle size D50 of the carrier particles in the lower coating layer.

[0104] FIG. 7 shows the relationship between the average particle diameter D50 of the carrier particles of the lower coat layer and the amount of HC emissions in Comparative Examples 1 and 2 and Examples 1 and 3 to 5. From Table 1 and FIG. 7, it was found that the HC purification performance was improved by increasing the average particle diameter D50 of the lower coat layer / upper coat layer from Example 1 to Example 3. On the other hand, it was found that the HC purification performance was reduced by further increasing the average particle diameter D50 from Example 3 to Comparative Example 2. This is because the advantage of increasing the average particle diameter D50 of the lower coat layer / upper coat layer is that the HC purification performance is improved by suppressing the alloying of Pd and Rh, but the disadvantage is that the HC purification performance is reduced due to the promotion of particle growth due to the durability of Pd due to the decrease in the specific surface area of ​​the upper coat layer. Therefore, it is considered that the latter effect was large in Example 5 and Comparative Example 2, and the HC purification performance was reduced on the contrary. Therefore, it is preferable that the average particle diameter D50 of the lower coat layer is 5 μm to 16 μm, which has a higher HC purification performance than Comparative Example 1. [Explanation of symbols]

[0105] 1: substrate, 2: catalyst coating layer, 3: lower coating layer, 4: upper coating layer

Claims

1. A catalyst for purifying exhaust gas, comprising a substrate and a catalyst coating layer coated on the substrate, The catalyst coating layer has an undercoat layer coated on the substrate and an upper coating layer coated on the undercoat layer, The upper coating layer contains Pd and / or Pt and first support particles, The first support particles are Al 2 O 3 Including, 80% by weight or more of the total weight of Pd and / or Pt contained in the upper coating layer is Al 2 O 3 It is supported by the ratio of the thickness of the upper coating layer to the thickness of the lower coating layer (upper coating layer / lower coating layer) is 0.2 or less; the lower coating layer contains Rh and second carrier particles; The average particle size D50 of the second carrier particles is 5 μm to 16 μm, The local degree of Rh contained in the lower coating layer is represented by the following formula: Local degree of Rh=1 / Uniform degree of Rh (In the formula, "degree of uniformity of Rh" is 1-(number of cells with a value of 0 / total number of cells), where "number of cells with a value of 0" refers to the total number of cells with a value of 0 out of the total cells in the lower, central and upper parts when a 200 x 200 cell portion is cut out from the csv data, which is the original data of the EPMA image from which Rh is extracted at 500x magnification of the lower coating layer, and a 50 x 50 cell lower, central and upper portion is cut out from the cut out portion, and "total number of cells" refers to the total number of cells in the lower, central and upper parts.) is arranged so that it is 1.47 to 2.

10. Catalyst for purifying exhaust gas.

2. 2. The exhaust gas purifying catalyst according to claim 1, wherein the average particle diameter D50 of the first carrier particles is equal to or greater than the average particle diameter D50 of the second carrier particles.

3. 95% by weight or more of the total weight of Pd and / or Pt contained in the upper coating layer is Al 2 O 3 The exhaust gas purifying catalyst according to claim 1 , wherein the catalyst is supported on a carbon nanotube.

4. 2. The exhaust gas purifying catalyst according to claim 1, wherein the upper coat layer has a thickness of 20 μm or less.

5. A method for producing the exhaust gas purification catalyst according to any one of claims 1 to 4, (i) stirring and mixing a precursor of Rh, a second support particle, and a solvent, and drying and calcining the resulting mixture to obtain Rh-loaded support particles; (ii) a step of stirring and mixing the Rh-supported support particles obtained in the step (i), the second support particles not supporting Rh, and a solvent, and pulverizing the second support particles so that the average particle size D50 of the second support particles is 5 μm to 16 μm, thereby preparing a catalyst coating layer slurry for a lower coating layer; (iii) applying the catalyst coating layer slurry for the undercoat layer obtained in the step (ii) onto a substrate, and drying and firing the catalyst coating layer to form an undercoat layer; (iv) Pd and / or Pt precursors, Al 2 O 3 and a solvent to prepare a catalyst coating layer slurry for an upper coating layer; (v) a step of coating the catalyst coating layer slurry for an upper coating layer obtained in the step (iv) on the substrate on which the lower coating layer obtained in the step (iii) is formed, followed by drying and firing to form an upper coating layer; The method includes:

Citation Information

Patent Citations

  • Exhaust gas purifying catalyst and its manufacturing method

    JP2007313498A

  • Exhaust gas purification catalyst for automobile

    JP2019069402A